Pengaruh Harga, Loyalitas Merek, Citra Merek, Kualitas Produk, dan Viral Marketing Terhadap Keputusan Pembelian Skincare Skintific di Kalangan Kampus - Putri Anggraini; Yuniorita Indah Handayani; Haifa (CV. ITTC INDONESIA, 2025)
This study focuses on the campus community, specifically students of the Mandala Institute of Technology and Science in Jember, as the object of research. The study examines variables such as price, brand loyalty, brand image, product quality, and viral marketing, which are believed to influence Skintific skincare purchasing decisions. Using a quantitative method, the research employed data analysis techniques including Instrument Testing, Classical Assumption Testing, Multiple Regression Analysis, Coefficient of Determination (R²), and Hypothesis Testing (t-test and F-test). A non-probability sampling method was applied by combining purposive and accidental sampling, resulting in 60 respondents. Data analysis was conducted using SPSS version 20. The results show that price, brand loyalty, product quality, and viral marketing partially influence purchasing decisions, while brand image does not. Simultaneously, all five variables significantly influence purchasing decisions for Skintific skincare among students.